Algorithm and architecture of low computation FSHEXBS motion estimation for wireless video sensor networks - Cheong, Seong Chee (School of Microelectronic Engineering, Universiti Malaysia Perlis, 2017)
The main objective of this project is to design a low computation motion estimation module with good image quality for wireless sensor networks application. To achieve this, the following items should be completed as well ; to study existing Fast Search motion estimation algorithms and analyze them based on image quality and computational cost ; to enhance existing Fast Search motion estimation algorithm to have lower computational cost while the image quality can be assured ; to design the algorithm by using Matlab and C code to run simulation in order to obtain experimental results for comparison purpose ; to design motion estimation architecture by using Verilog programming and simulate it.